A Case for Interaction between Hospital Librarians and Administration. Issue 4 (1st October 2016) - Pylarinou, Stamatoula; Kapidakis, Sarantos
ABSTRACT: Scholarly publishing of hospital personnel is a way of highlighting research and clinical work. It is a result of intense clinical practice and it includes data evaluated by the scientific community. Usually, bibliographic data are used to assist information extraction, information dissemination as well as scientific excellence. In this study we use bibliographic data to provide useful info to other parts of the hospital community, such as administration or patients. Data extracted from MEDLINE/PubMed bibliographic database of scientific publications are edited and used to answer some sample questions.